Maternal mortality: a retrospective analysis of 6 years in a tertiary care centre - Parmar, Monika; Shriastava, Sushruta; Kanhere, Anjali; Patel, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy, although being considered a physiological state, carries the risk of serious maternal morbidity and at times death. This is due to various complications that may occur during pregnancy, labour or thereafter. Worldwide 3,03,000 women are dying of pregnancy related complication annually. Methods: The medical records of all maternal death occurred over a period of last five years between August 2011 to August 2017 in the Department of Obstetrics and Gynaecology at our tertiary care hospital were reviewed and analysed. Results: It is observed that out of total 30 patients, 24 (80%) deaths were from 20-30 year of age followed by 5 (16.67%) deaths from above 30 years of age. In the study period, 40% of maternal deaths were due to direct causes, haemorrhage (8/12; 66.67%) was main direct causes of obstetric death. Conclusions: The complications leading to maternal death can occur without warning at any time during pregnancy and childbirth. Most maternal deaths are preventable by optimum utilization of existing maternal and child health care facilities. Complications require prompt access to quality obstetric services equipped with life-saving drugs, intensive care unit, and the ability to provide blood transfusions and to perform surgical interventions as per the need.